Analysis of athletic performance and personality type of University of Wisconsin-La Crosse footbal players for 1984 - Miyamoto, Michael (My University, 1985)
The Myers-Briggs Type Indicator (MBTI) has become a very popular inventory in the fields of academic and vocational counseling. Even the skeptics, who argue that the MBTI does not represent a successful operationalization of Jungian concepts, agree that the instrument has potential in the counseling field. The analysis of type configurations can aid an individual in choosing a course of study or an eventual career. This study attempted to determine if the MBTI could be used to reveal an association between athletic preference and success and type. It specifically examined 53 members of the 1984 UW-La Crosse football team. Part I of the study sought to determine if there were player distinctions on selected attitudes (J/P) and functions (T/F) of the MBTI. Part II specifically investigated the various football team positions to see if there were associations between selected MBTI preferences and the coaches' performance ratings. It was concluded that at the .05 level, a significant number of Perceiving types existed on the 1984 UW-La Crosse defensive squad. It was also discovered at the .001 level that a very significant number of student/athletes on the UW-La Crosse football team preferred the Thinking over the Feeling function. Part II of the study revealed two strong positive correlations between the strength of preference on the Thinking function and the coaches? performance rating for the positions of running back (0.9949) and defensive back (0.6170). It was concluded that a larger sample population would be needed in order to determine if there truly is an association between strength of preference scores and athletic performance.
Keywords: University of Wisconsin--La Crosse -- Football; Football players -- Wisconsin -- La Crosse